Molecular cloning and structural analysis of a gene from Zea mays (L.) coding for a putative receptor for the plant hormone auxin. - Hesse, T (1989)
The major auxin-binding protein from maize coleoptiles was purified to homogeneity. The protein has an apparent mol. wt of 22 kd and binds 1-naphthylacetic acid with a KD of 2.40 x 10(-7) M. Additional antigenically related proteins, present in very low amounts, could be demonstrated in maize coleoptiles using immunodetection. Extensive protein sequence analysis of the major auxin-binding protein allowed the construction of several synthetic oligonucleotide probes which were used to isolate a cDNA coding for this protein. The cDNA corresponds to a mRNA with a 3'-poly(A)+ sequence and a single, long open reading frame of 603 bases. The open reading frame, starting 34 residues from the 5' end of the cDNA, predicts a 21,990 Dalton protein of 201 amino acids. Comparison of this deduced amino acid sequence with the partial amino acid sequences of purified auxin-binding protein, revealed a perfect match, involving a total of 53 amino acid residues. The primary amino acid sequence includes a 38-amino-acid-long N-terminal hydrophobic leader sequence which could represent a signal for translocation of this protein to the endoplasmic reticulum. An additional signal is located at the C-terminal end, consisting of the amino acids KDEL known to be responsible for preventing secretion of proteins from the lumen of the endoplasmic reticulum in eucaryotic cells. The primary sequence contains a N-glycosylation site (-asp133-thr-thr-). This site was found to be glycosylated by a high-mannose-type oligosaccharide.(ABSTRACT TRUNCATED AT 250 WORDS)